The Image of Digital China in the Russian Media - Lijun Guo (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The texts published in the Russian mass media on the digitalization processes in China are analysed in the article. The relevance of the study is due to the attention of the Chinese government to the implementation of international cooperation with various countries, including Russia. It is noted that the “Chinese theme” is one of the most relevant in Russian publications. Attention is paid to one of the most popular and dynamically developing areas — digitalization. The author proceeds from the assumption that the media not only reflect news information, but also in a certain way form ideas about a particular object being described. The author notes that significant attention is paid to the development of digitalization in the PRC in Russian newspapers and magazines. It is shown that in the publications of the Russian media, China is represented by one of the world leaders in digitalization, which is supported by the state and its citizens. The contexts, indicating that digitalization is penetrating into different spheres of the country’s life: education, industry, trade, etc., are given. The author comes to the conclusion that an exclusively positive image of digital China is being constructed in the Russian media.